CFD Analysis Of Helical Screw Tape Of Heat Exchanger For Laminar Flow - et. al., Ravi Shankar Kumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The heat emission from heat exchangers is of great importance for the efficient and economical operation of industrial machines. The main focus of the study is to increase the overall heat transfer rate and optimize the design. And the Nusselt number and Reynolds number calculated using ANSYS Fluent. And the helical screw inserts save energy. A CFD study of the helical band insert with different twist ratio in the tube was performed for laminar flow as a heat transfer amplifier using commercial software. This use increased the rate of heat transfer with a significant increase in pressure drop. In this study, 3 types of helical belts were used to add value to HTC. The value of the friction factor increases with increasing Reynolds number. The value of HTC increases as the Reynolds number increases. The HTC goes up to 1562.5,1666,1886.79 in all three cases. The Nusselt number and Reynold number increase to 94.33 and 1997.5, respectively. In case 3 The temperature of the pipe wall is reduced if a pipe with an insert is used, which means less irreversibility and greater heat transfer properties. It has a relatively higher and lower temperature spiral profile in the pipe wall as the insert twist.